The Effect of education based on Awareness and Performance of hospitals service personnel about protective behaviors against the harmful effects of detergents and disinfectants - Elham Damani; Khadijah Dehghan Bakhshani; Mohammad Hadi Abbasi; Tahmineh Karimzaei; Nasrin Rezaee; Zaynab Borhanzahi (Mashhad University of Medical Sciences, 2017)
Background and objective: The individual protective behaviors have essential role in prevention or decrease the incidence of the harmful effects of detergents. This study aimed to determine the Effect of education based on Awareness on the harmful effects of detergents and disinfectants on hospital service personnel. Methods: This Quasi-experimental study was conducted on 100 off hospital service personnel that randomly divided to control and Intervention groups. Data collection tool was a Multi-section questionnaire includes demographic, Awareness and practice, that its validity and reliability was confirmed by expert and Cronbakh Alpha test. After primary data collecting, educational intervention performed and two months later data in both groups was collected again and analyzed in spss16 soft-ware using descriptive and analytical statistics. Results: Results showed that after intervention only in experimental group the mean scores of Awareness off 12/82±2/42 with 18/06±3/25 and preventive behaviors on hospital service personnel off 14/50    ± 3/41 with 20/06 ± 3/76 meaningful increased. Conclusion: The results showed that education intervention based on Health education was useful in increasing Awareness and promoting preventive behaviors of detergents and disinfectants on hospital service personnel Paper Type: Research Article.